1991
DOI: 10.1093/oxfordjournals.aje.a116070
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electric Blankets and Risk of Postmenopausal Breast Cancer

Abstract: Chronic exposure to 60-Hz electromagnetic fields has been hypothesized to increase breast cancer risk by suppressing the normal nocturnal rise in pineal melatonin. From 1987 to 1989 in western New York the authors investigated the use of electric blankets as a risk factor for breast cancer in a case-control study of postmenopausal women aged 41-85 years. A study population of 382 cases and 439 randomly selected community controls was queried regarding use in the previous 10 years, the frequency of use by seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 0 publications
2
43
0
1
Order By: Relevance
“…Furthermore, exposure typically takes place at night when the natural melatonin peak occurs and the blanket is placed close to the body. Vena and coworkers performed a case-control study focusing on exposure to electric blankets (114,115). They found that the use of electric blankets continuously throughout the night was associated with a nonstatistically significant increase in postmenopausal breast cancer (OR = 1.46, 95%CI = 0.96-2.20) (115) and for premenopausal breast cancer (OR = 1.43, 95%CI = 0.94-2.17) (114) compared to never users.…”
Section: Other Epidemiological Studiesmentioning
confidence: 99%
“…Furthermore, exposure typically takes place at night when the natural melatonin peak occurs and the blanket is placed close to the body. Vena and coworkers performed a case-control study focusing on exposure to electric blankets (114,115). They found that the use of electric blankets continuously throughout the night was associated with a nonstatistically significant increase in postmenopausal breast cancer (OR = 1.46, 95%CI = 0.96-2.20) (115) and for premenopausal breast cancer (OR = 1.43, 95%CI = 0.94-2.17) (114) compared to never users.…”
Section: Other Epidemiological Studiesmentioning
confidence: 99%
“…Studies have been established to explore both pre-menopausal (Vena et al, 1994) and post-menopausal breast cancer in conjunction with electric blanket use (Vena et al, 1991;McElroy et al, 2001). However, currently no association to breast cancer risk has been reported in either pre-or post-menopausal women using electric blankets (Gammon et al, 1998;Laden et al, 2000;Zheng et al, 2000b;Kabat et al, 2003).…”
Section: Breast Cancermentioning
confidence: 99%
“…The effects of electric blanket use were considered in one case-control study each of postmenopausal (137) and premenopausal breast cancer (138). A small, nonsignificant increased risk was seen in both pre-and postmenopausal women for continuous use of electric blanket throughout the night compared to never use.…”
Section: Adult Cancermentioning
confidence: 99%